This preview shows page 1. Sign up to view the full content.
Unformatted text preview: be a last resort.) Here, it is a square root function. Let f 1 x ( ) = x . Basic Graph: y = x Graph: y = x + 3 Begin with: f 1 x ( ) = x Transformation: f 2 x ( ) = f 1 x + 3 ( ) Effect: Shifts graph left by 3 units Graph: y = x + 3 Graph: y = x + 3 + 2 Transformation: f 3 x ( ) = f 2 x ( ) Transformation: f 4 x ( ) = f 3 x ( ) + 2 Effect: Reflects graph about x-axis Effect: Shifts graph up by 2 units...
View Full Document
- Spring '09